THE USE OF SCANNING ACOUSTIC MICROSCOPE FOR FLAW DETECTION IN METALLIC MATERIALS (Jurnal Mekanikal, 2018)
The main objective of this paper is to understand the principles andtheories behind the operation of the equipment, and its architecture.The advantages and limitations of the scanning acoustic microscopeare also investigated by imaging a set of samples. The principle ofoperation of a scanning acoustic microscope is producing magnifiedacoustic images of the surface or interior of a solid by passing highfrequencyfocused acoustic pulses through the material anddisplaying the received signal in the image fo rm as shades of grey.The Significant advantage to be- gained in using scanning acoust icmicroscope fo r producing images are the ability of acoustic wQ\'es topenetrate opaque material and the distinctive origin ofcontrast in themechanical properties of the specimen, Three. sets of samples areobserved under the scanning acoustic microscope and they areVickers hardness indention samples. quenched samples and porositysamples. It is found that the results obtained for the samples aresubjected to the overall ability of the equipment used. The operatingfrequency was one of the most significant limiting factors in thiswork, as the resolution obtained was not as high as would befavourable. However, satisfactory images with distinctive contrast
Keywords: Keywords